2016
DOI: 10.1134/s0031918x16070139
|View full text |Cite
|
Sign up to set email alerts
|

Structure and fracture mechanism of a two-phase chromium–nickel alloy during high-temperature deformation

Abstract: Abstract⎯The structure and mechanical properties of a two-phase Kh65N33V2FT alloy has been studied after tests at room and high temperatures. The morphology of the main phases, namely, solid solutions of nickel in chromium (α) and chromium in nickel (γ), is changed depending on temperature. The lattice parameters of the main phases have been determined. The main mechanism of deformation for this alloy is shown to be grain-boundary sliding. Bulk and grain-boundary diffusion creep and self-regulating diffusionvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The SEM showed that with temperature increase the morphology of the phases also significantly changed. Although at test temperature of 20 °C the difference in the microstructure of the alloys is insignificant, with temperature increase in alloy I take place coarsening of the secondary precipitations of γ-Ni solid solution in α-Cr solid solution due to the dynamic recrystallization [10] (Fig. 4c, e).…”
Section: Resultsmentioning
confidence: 98%
“…The SEM showed that with temperature increase the morphology of the phases also significantly changed. Although at test temperature of 20 °C the difference in the microstructure of the alloys is insignificant, with temperature increase in alloy I take place coarsening of the secondary precipitations of γ-Ni solid solution in α-Cr solid solution due to the dynamic recrystallization [10] (Fig. 4c, e).…”
Section: Resultsmentioning
confidence: 98%